Relationship between mean platelet volume elevation and left ventricular mass index in hypertensive patients - Yavuzkir, Mustafa Ferzeyn; Kurtoglu, Ertugrul; Yilmaz, Mucahid; Korkmaz, Hasan; Cakmak, Tolga; Dogdu, Orhan; Akbulut, Mehmet (Sage Publications Ltd, 2014)
Objectives: To compare the mean platelet volume (MPV; a general marker of platelet activation) in groups of patients with and without hypertension and to analyse its relationship with left ventricular mass index (LVMI). Methods: This cross-sectional, observational study enrolled newly diagnosed patients with untreated stage I-II hypertension and healthy control subjects without hypertension. MPV was measured using a haematology analyser. Echocardiography was performed on all of the study participants. Results: A total of 50 newly diagnosed patients with hypertension and 50 healthy control subjects were enrolled in the study. The majority of the demographic characteristics and laboratory findings were not significantly different between the two groups. The mean +/- SD MPV was significantly higher in the hypertensive group compared with the control group (10.3 +/- 1.4 fl versus 9.2 +/- 1.8 fl, respectively). The mean +/- SD LVMI was significantly higher in the hypertensive group compared with the control group (115.9 +/- 23.0 g/m(2) versus 95.7 +/- 23.4 g/m(2), respectively). There was no significant correlation between MPV and LVMI. Conclusion: In patients with untreated hypertension, despite elevated MPV levels there was no correlation between LVMI and MPV.
Keywords: Hypertension; mean platelet volume; left ventricular mass index